A method for seedling recovery in Jatropha curcas after cryogenic exposure of the seeds. - de C. Silva, Rafael; Camillo, Julcéia; Scherwinski-Pereira, Jonny E. (Revista de Biología Tropical, 2012)
Actually, the germplasm of Jatropha spp. is conserved as whole plants in field collections. Under this storage method, the genetic resources are exposed to disease, pest and natural hazards such as human error, drought and weather damage. Besides, field genebanks are costly to maintain and with important requirements of trained personnel. Thus, the development of efficient techniques to ensure its safe conservation and regeneration is therefore of paramount importance. In this work we describe a method for Jatropha curcas seeds cryoexposure and seedling recovery after thawed. In a first experiment, an efficient protocol for in vitro plant recovery was carried out using zygotic embryo or seeds with or without coat. In a second experiment, desiccated seeds with or without coat were exposed to liquid nitrogen and evaluated after cryoexposure. Germination percentages were variable among treatments, and seeds demonstrated tolerance to liquid nitrogen exposure under certain conditions. Seeds of J. curcas presented up to 99.6% germination after seed coat removal. Seeds with coat cultured in vitro did not germinate, and were 60% contaminated. The germination of the zygotic embryos was significantly higher in the ½ MS medium (93.1%) than in WPM medium (76.2%), but from zygotic embryo, abnormal seedlings reached up to 99%. Seeds with coat exposed to liquid nitrogen showed 60% germination in culture after coat removal with good plant growth, and seeds cryopreserved without coat presented 82% germination, but seedlings showed a reduced vigor and a significant increase in abnormal plants. Seeds cultured in vitro with coat did not germinate, independently of cryoexposure or not. This study reports the first successful in vitro seedling recovery methodology for Jatropha curcas seeds, after a cryopreservation treatment, and is recommended as an efficient procedure for in vitro plant recovery, when seeds are conserved in germplasm banks by low or cryotemperatures.